Microbial Studies of Tetrathioazoic Acid and Its Complexes with Cu(I), Cu(II) and Si(IV) Compounds - Jadon, S.P.S.; Shalini (Asian Journal of Chemistry, 2010)
Tetrathioazoic acid (L) and its complexes synthesized with Cu(I), Cu(II), Si(IV) were treated against E. coli and S. typhimurium gram negative bectria and C. albicans and C. neoformans fungi. The ligand is found effective against E. coli and C. neoformans, while the complexes Cu(I) L2 and Cu(II) L1 show better effectiveness against all except C. albicans. The complex of Si(IV) is best bactericidal and fungicidal.